Accessible and meaningful engagement for people living with dementia when transitioning arts activities online. (20th December 2022) - Christensen, Justin; MacRitchie, Jennifer; Timmers, Renee
Abstract: Background: With opportunities for self‐expression and enjoyment, creative arts activities can offer many benefits for people living with dementia including improving health and wellbeing. During the COVID‐19 pandemic, arts organizations have had to transition activities previously involving face‐to‐face interactions to remote delivery. Aiming to understand the accommodations that have been made for people living with dementia (PLWD) to access arts activities through technology, we conducted a survey with arts‐workers involved in the remote delivery. Method: A survey using a mixture of qualitative and quantitative questions was distributed online to arts workers delivering activities remotely for PLWD in the UK during the COVID‐19 pandemic. These included what types of activities were employed, how the activities changed due to remote access (including motivations for access), what tools were used, what technological support there was for access, and how this affected the number of people they were able to reach with these activities. Results: Twenty‐seven arts workers (mean age = 47 SD = 6.4) delivering music (23 respondents), arts (8), crafts (4), dance (6), drama (3), and word‐based activities (1) responded. The main tools used included: Zoom, YouTube Live, Microsoft Teams, and Facebook Live. Several themes emerged from the thematic analysis of open‐ended responses: i) gaining a sense of community, finding structure and purpose, and combatting against physical isolation were perceived to be major motivations for people living with dementia, ii) creating opportunities for choosing, contributing input, and sharing was important, and iii) changes in access resulted from the shift to remote delivery such as difficulty for PLWD to interact through technology, user setup and maintenance needs, and the possibility for geographic expansion of the remote service. Conclusions: The findings highlight the diverse, individual needs of people living with dementia in group arts participation, while still prioritizing their motivations for participation including sense of community, structure, purpose, and combatting against feelings of isolation during the pandemic. Particularly successful remote activities gave opportunities for meaningful contribution and had a multitude of possibilities for access for PLWD.